Optical Coherence Tomography Angiography (OCTA) Analysis of Perifoveal Capillary Arcade in Patients with Retinal Vein Occlusion Treated with Anti-VEGF - Wajid, Nida; Muzaffar, Waqar; Arain, Muhammad Aamir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the changes in perifoveal capillary arcade in patients with retinal vein occlusion treated with intravitreal injections of anti-vascular endothelial growth factor for macular edema resulting from retinal vein occlusion with OCTA.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jul 2018 to Jul 2019.Methodology: Patients diagnosed as case of retinal vein occlusion underwent complete eye examination. Optical coherence tomography angiography (OCTA) was done in all the patients. Patients having macular edema were prescribed intravitreal anti-vascular endothelial growth factor inhibitors on monthly basis. OCTA was repeated at the third month.Results: In this study, 50 eyes were evaluated. After treatment patients having perifoveal capillary arcade of less than two quadrants increased from 47.7-68.8% (p